TAHAP CORE ABILITIES DALAM KALANGAN PELAJAR BIDANG KIMPALAN DAN FABRIKASI LOGAM ILP NEGERI JOHOR - Amiruddin, Mohd Hasril; Azemi, Amira Eleza (Online Journal for TVET Practitioners, 2018)
Core Abilities is the core skills that should be present in every workers especially in a working situation. The globalisation era requires the mastery of Core Abilities towards employment of jobs, mainly in work force that consists of people who are knowledgeable, attitude and skilled. Therefore, the research is aimed towards surveying the mastery of Core Abilities among ILP students around Johor. Research samples include 105 students of final year certificates from â€œKimpalan dan Fabrikasi Logamâ€ course. This research used quantitative and the instrument used are questionnaires that are constructed based on the Core Abilities Stage 3 module that includes effective communication, ICT awareness, leadership skills, workplace ethics, administrator skills, and health and environmental awareness. The data of the research were analysed using the Statistical Package for Social Science (SPSS) software to calculate the percentage, min, standard deviation and T-Test. The research result shows that the mastery of Core Abilities with gender have yield results of high mastery of Core Abilities that are equal for both men and women. In conclusion, students need to master the Core Abilities to increase competition in the work opportunities